Penerapan Model Pembelajaran dalam Pendidikan Agama Kristen Untuk Meningkatkan Mutu Belajar Peserta Didik - Esti Regina Boiliu (REAL DIDACHE: Journal of Christian Education, 2022)
Improving the quality of learning is an important thing that should be done in an education. In the education system, the learning process is based on Christian religious education, in addition to improving the quality of learning for students to be able to compete not only nationally, but internationally, both intellectually and spiritually. The purpose of this study is to see how the use of learning models in the implementation of Christian religious education can be used as a strategy in improving the quality of student learning. The writing of this scientific article uses a qualitative method, where the author takes data from various sources such as books, journals, newspapers, the internet and other scientific articles that have been systematically selected and researched according to the interests of writing this article. The results of this study are to suggest about several learning models that can be applied in the learning process of Christian religious education to help improve the quality of student learning.Keywords: learning model; learning quality; Christian educationAbstrakPeningkatan mutu belajar merupakan hal penting yang semestinya dilakukan dalam suatu pendidikan. Dalam sistem pendidikan, proses pembelajaran berbasis pendidikan agama Kristen, selain meningkatkan kualitas mutu belajar peserta didik untuk mampu berdaya saing bukan hanya secara nasional, melainkan internasional baik secara intelektual maupun spiritual. Tujuan penelitian ini ialah untuk melihat bagaimana penggunaaan model-model pembelajaran dalam pelaksanaan pendidikan agama Kristen yang dapat dijadikan sebagai strategi dalam peningkatan mutu belajar peserta didik. Penulisan artikel ilmiah ini menggunakan metode kualitatif, di mana penulis mengambil data dari berbagai sumber seperti buku, jurnal, koran, internet dan artikel ilmiah lainnya yang telah dipilih dan diteliti secara sistematis sesuai dengan kepentingan penulisan artikel ini. Hasil penelitian ini adalah mengemukakan tentang beberapa model pembelajaran yang dapat diterapkan dalam proses pembelajaran pendidikan agama Kristen untuk membantu meningkatkan mutu belajar peserta didik.Kata kunci: model pembelajaran; mutu belajar; pendidikan agama Kristen